В. Н. Топоров. Знак и текст в пространстве и времени. Публикация М. Д. Дынина и Т. В. Цивьян [Vladimir Toporov. Sign and Text in Space and Time (Publication by Mikhail Dynin and Tatiana Civjan)] - Toporov, Vladimir (Slavica Revalensia, 2015)
“Знак и текст в пространстве и времени” (“Sign and Text in Space and Time”) is a previously unpublished scholarly autobiography by one of the most learned, erudite, and prominent 20th century Russian scholars, Vladimir Toporov (1928–2005). It contains a detailed account of the scholar’s major achievements in various fields of knowledge: from Indo-European studies to the history of Russian literature.